Geotecnologias aplicadas à análise ambiental: aquisição e avaliação de variáveis espectrais da vegetação entre os anos de 2018 e 2019 na Bacia Hidrográfica do Ribeirão das Cruzes, Selvíria/MS - Alisson Rodrigues Santori (2021)
The present study is motivated by the application of different techniques that integrate geotechnologies and, thus, to contribute to the improvement of environmental analysis and monitoring research in Brazilian natural resources management units. The main objective is to obtain data to assess the quality of natural resources in the watershed, observing orbital products and using thematic mapping techniques, in addition to the application and interpretation of radiometric indices and image processing. This study also discusses data validation and means of proving the integrated capability of managing environmental information in areas of relevant interest to planning. The river basin of Ribeirão das Cruzes-MS, Brazil, was the unit and the chosen cutout for the application of the environmental analysis of these resources, thus, part of its components is characterized and represented by the set of data explored in this study. The conceptual and theoretical basis of the General Systems Theory (GST), the temporal and seasonal monitoring of components of the physical environment, the qualitative analysis of natural resources in hydrographic basins and the use of technical and functional tools of geotechnologies, are the starting point of this analysis. The main resource explored in this environmental analysis are the forms of vegetation that occupy the BHRC area, mainly the forms of native vegetation and their dynamics. The indicators used to carry out this process are considered to be highly representative of flow exchange processes between components of the watershed environmental system. The form of analysis of these products and the application of these techniques in the proposed methodology, follow indications of studies with important concepts and environmental applicability, associating the use of geoprocessing and automatic tools based on Geographic Information Systems (GIS). In this work, multi-temporal and seasonal images from two subsequent years were used as a basis for performing digital image processing (PDI) in the composition of land use and land cover, and for the production of the NDVI vegetation index, derived from land use techniques. equation of bands with opposite spectral behavior on certain targets. The results should meet the search for complementation and integration between the possibilities of thematic mapping, data acquisition and parameters in Remote Sensing. In short, the present study proposed the analysis of the modification capacity of the environmental system under certain conditions and influences and the effective possibility of monitoring and validating these variations, using databases and specific applications for the treatment of spatial and geographic information.